2021
DOI: 10.1038/s41419-021-04306-2
|View full text |Cite
|
Sign up to set email alerts
|

Fin56-induced ferroptosis is supported by autophagy-mediated GPX4 degradation and functions synergistically with mTOR inhibition to kill bladder cancer cells

Abstract: Ferroptosis is a form of regulated cell death that emerges to be relevant for therapy-resistant and dedifferentiating cancers. Although several lines of evidence suggest that ferroptosis is a type of autophagy-dependent cell death, the underlying molecular mechanisms remain unclear. Fin56, a type 3 ferroptosis inducer, triggers ferroptosis by promoting glutathione peroxidase 4 (GPX4) protein degradation via a not fully understood pathway. Here, we determined that Fin56 induces ferroptosis and autophagy in blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(102 citation statements)
references
References 61 publications
4
98
0
Order By: Relevance
“…Pretreatment with FG-4592, an inhibitor of prolyl hydroxylase of HIF, reduces renal injury via AKT/GSK-3β-mediated activation of Nrf2 in advanced stages of ferroptosis [ 32 ]. In addition, Yadong Sun et al reported that cancer spheroids proliferate using mammalian targets of rapamycin (mTOR) and utilize the lipid peroxidase GPX4 against ferroptosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with FG-4592, an inhibitor of prolyl hydroxylase of HIF, reduces renal injury via AKT/GSK-3β-mediated activation of Nrf2 in advanced stages of ferroptosis [ 32 ]. In addition, Yadong Sun et al reported that cancer spheroids proliferate using mammalian targets of rapamycin (mTOR) and utilize the lipid peroxidase GPX4 against ferroptosis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that FRGs are involved in the regulation of drug-induced ferroptosis in BLCA ( 11 ). Additionally, FRG-related inducers have been found to suppress BC with the help of mTOR inhibitors ( 19 ). Recently, ferroptosis participates in the inhibition of cell cycle in BC by obstructing the G0/G1 phase ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al. showed that FIN56 can induce ferroptosis in bladder cancer cells and can be enhanced by combination with the mTOR inhibitor, Torin 2 ( 143 ). Zhang et al.…”
Section: Caspase-independent Rcd In Targeted Therapymentioning
confidence: 99%